Leader Reinforcement Behaviors And Employee Work Outcomes: The Mediating Role Of Leader-Member Exchange - Tng, Chee Chow (2006)

(untitled)
Pimpinan adalah salah satu tajuk yang paling dikaji dalam sastera pengurusan.